2016
DOI: 10.1016/j.pharep.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

β-Elemene induces apoptosis of human rheumatoid arthritis fibroblast-like synoviocytes via reactive oxygen species-dependent activation of p38 mitogen-activated protein kinase

Abstract: Taken together, β-elemene is effective in inducing mitochondrial apoptosis of RA-FLS, which is mediated through induction of ROS formation and p38 MAPK activation. β-Elemene may thus have therapeutic benefits for RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…have reported that p38 MAPK can be activated by serum amyloid A, which is highly expressed in autoimmune disease, to be involved in the angiogenic process of RA. Meanwhile, Zou et al . has reported that activated p38 MAPK can induce β‐elemene to induce mitochondrial apoptosis of RA fibroblast‐like synoviocytes.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that p38 MAPK can be activated by serum amyloid A, which is highly expressed in autoimmune disease, to be involved in the angiogenic process of RA. Meanwhile, Zou et al . has reported that activated p38 MAPK can induce β‐elemene to induce mitochondrial apoptosis of RA fibroblast‐like synoviocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[110]. β-Elemene (30) is a known natural sesquiterpene compound, treatment with β-Elemene (10-200 µg/mL) can improve the phosphorylation level of p38 and promote cell apoptosis in RA-FLS, and p38 inhibitors can significantly reverse the pro-apoptotic effect of β-Elemene, consequently these results suggested that the MAPK pathway is closely involved in the pro-apoptotic effects of β-Elemene on RA-FLS [111].…”
Section: Mapk Mediated Apoptotic Pathwaymentioning
confidence: 91%
“…HFLSs participate in the development and progression of RA by producing cytokines and proteases that contribute to cartilage destruction (18). Apoptosis of HFLSs is currently considered as a potential therapeutic target for RA (19,20). Our study observed that IL-17 inhibited HFLSs apoptosis, while lncRNA CASC2 promoted HFLSs apoptosis by inhibiting IL-17.…”
Section: Discussionmentioning
confidence: 57%